Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1099/mic.0.000273
|View full text |Cite
|
Sign up to set email alerts
|

The phenotypic evolution of Pseudomonas aeruginosa populations changes in the presence of subinhibitory concentrations of ciprofloxacin

Abstract: Ciprofloxacin is a widely used antibiotic, in the class of quinolones, for treatment of Pseudomonas aeruginosa infections. The immediate response of P. aeruginosa to subinhibitory concentrations of ciprofloxacin has been investigated previously. However, the long-term phenotypic adaptation, which identifies the fitted phenotypes that have been selected during evolution with subinhibitory concentrations of ciprofloxacin, has not been studied. We chose an experimental evolution approach to investigate how exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 57 publications
8
27
0
Order By: Relevance
“…In P. aeruginosa, swimming motility is driven by a single unipolar flagellum which in PAO1 is dependent on 41 genes encoding structural/ assembly and regulatory components of the flagellar organelle (40). In accordance, phenotypic characterization of P. aeruginosa populations during planktonic experimental evolution showed a decrease in the swimming motility of the populations (41), and this was also confirmed in the present study (data not shown). This suggests that during evolution under conditions of good oxygenation and sufficient nutrition, swimming motility is probably an energy-expensive property that is easily lost.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In P. aeruginosa, swimming motility is driven by a single unipolar flagellum which in PAO1 is dependent on 41 genes encoding structural/ assembly and regulatory components of the flagellar organelle (40). In accordance, phenotypic characterization of P. aeruginosa populations during planktonic experimental evolution showed a decrease in the swimming motility of the populations (41), and this was also confirmed in the present study (data not shown). This suggests that during evolution under conditions of good oxygenation and sufficient nutrition, swimming motility is probably an energy-expensive property that is easily lost.…”
Section: Discussionsupporting
confidence: 91%
“…Intriguingly, mutations in the quorum-sensing system were not present in the CIP-evolved biofilm populations, indicating a selection for the maintenance of quorum-sensing-regulated factors under evolution at subinhibitory concentrations of CIP. In accordance, we have previously observed increased levels of quorum-sensing molecules in planktonic evolved populations in the presence of 0.05 mg/liter CIP compared to the controls (41). One explanation for these observations could be the protection conferred by QS-regulated catalases and superoxide-dismutases against antibiotic-related oxidative stress (44), as we have shown increased production of reactive oxygen species in P. aeruginosa biofilms exposed to ciprofloxacin (45).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although we have shown previously that phages can alter the mode and rate of adaptive evolution [26], comparable sets of phenotypes eventually occurred both in the presence and absence of phages. It is, however, worth noting that similar phenotypes can be driven by sub-inhibitory concentrations of antibiotics in non-biofilm systems [48]. In CF, it has been proposed that the maintenance of phenotypically diverse P. aeruginosa populations may be a consequence of the spatial heterogeneity of the lung, leading to regional isolation of separately evolving communities [15].…”
Section: Discussionmentioning
confidence: 99%
“…The frequent prescription of broad-spectrum antibiotics rather than prescribing more precise antibiotics and the inadequate dose and duration of treatment have been particularly embroiled. The subinhibitory concentrations resulting from the later effect can modulate the bacterial virulence [19,20]. A source of subinhibitory levels of antibiotic can be from the often neglected factor that generic drugs may not be in fact therapeutically equivalent to the branded antibiotic.…”
Section: Introductionmentioning
confidence: 99%